1988
DOI: 10.1159/000215841
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Abnormal Plasminogen, Frankfurt I, a Cause for Recurrent Venous Thrombosis

Abstract: A new abnormal plasminogen, Frankfurt I, has been identified in the plasma of a 42 year-old male patient who had recurring thromboses, thrombophlebitis and pulmonary embolism since his age of 29. Reduced functional and also slightly reduced antigen plasminogen concentrations were found in both the proposituts and his mother. Plasmin generation rates carried out by Streptokinase and Urokinase were also abnormal. The plasmin generated was very unstable in the absence of stabilizing ligands and/or substrates. Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Originally, several older studies have linked dysplasminogenemia with an increased risk for deep vein thrombosis [74,80,81]. However, later and more comprehensive studies have clearly demonstrated that isolated dysplasminogenemia is not a risk factor for thrombosis [26,82].…”
Section: Dysplasminogenemia (Type II Plg Deficiency)mentioning
confidence: 99%
“…Originally, several older studies have linked dysplasminogenemia with an increased risk for deep vein thrombosis [74,80,81]. However, later and more comprehensive studies have clearly demonstrated that isolated dysplasminogenemia is not a risk factor for thrombosis [26,82].…”
Section: Dysplasminogenemia (Type II Plg Deficiency)mentioning
confidence: 99%
“…Similarly abnormally elevated levels of histidine-rich glycoprotein or increased levels of alpha-2-antiplasmin are extremely uncommon in familial thrombophil ia (9,10). In contrast, the first reports linking familial dysplasminogenaemia (11) and hypoplasminogenaemia (12) with thrombosis were quickly corroborated by many similar publications (13)(14)(15)(16)(17)(18)(19)(20). However, in a review of 20 such families, Dolan and Preston (21) found that only one of 61 affected relatives had suffered a thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been much interest in the association between venous thrombosis and reduced levels of functioning PLG resulting from either a dysplasminogenaemic (1)(2)(3)(4)(5) or hypoplasminogenaemic state (6)(7)(8)(9)(10). Numerous cases of familial PLG deficiency have been described (10)(11)(12)(13)(14)(15)(16)(17), however, the link with thrombosis is tenuous since the propositus is often the only symptomatic family member.…”
Section: Introductionmentioning
confidence: 99%